Análise comparativa da reatividade anti-LID-1, NDO-LID, NDO-HSA e PGL-1 em Hanseníase - Angélica da Conceição Oliveira Coelho Fabri (2015)
The subclinical infection can be evaluated by serologic test which determine circulating immunoglobulins. The aim of this study was to analyze the reactivity of different antigens in leprosy cases, household contacts of index cases and the population of the endemic area toidentify the best antigen for the diagnosis of leprosy and detection of individuals infected with Mycobacterium leprae. It is a cross-sectional study of exploratory and analytical nature. The reactivity anti-LID-1, NDO-LID, NDO-HAS e PGL-1 were evaluated using the enzymelinkedimmunosorbent assay. The whole blood in Whatman filter paper of 2494 individuals from the general population of seven municipalities in the micro-Almenara and serum of 94 patients with leprosy and 104 household contacts of patients residing in Uberlândia wereanalyzed. The database was created in Epi Info software version 3.5.1 and analysis in the software Statistical Package for Social Sciences for Windows 18 and GraphPad Prism version 5. For statistical analysis the following tests were used: Kolmogorov-Smirnov, Kruskal Wallisone-way (H), Mann-Whitney (U) with Bonferroni correction, kappa, Spearman (rho), chisquare test of Pearson and binary logistic regression. Identied higher seropositivity in the group of MB patients, household contacts of MB patients and in individuals living in themunicipalities of Almenara and Jequitinhonha. Observed positive correlation between serology test and bacterial index, substantial agreement and significant in patients positive and positive correlation for all antigens. The LID-1 and NDO-LID antigens showed greater abilityto identify household contacts or the general population infected with M. leprae, but the performance of the NDO-LID was better. The native PGL-1 had higher seropositivity than the NDO-HSA for all clinical forms of leprosy and household contacts. The seropositivity prevalence in the general population was higher than the detection rate of leprosy cases in all evaluated municipalities. The age, family income, living in a city endemic, knowing someone who had or has leprosy, had or have the case in the family and live or lived with leprosy case are factors that can explain the anti-NDO-LID seropositivity difference. Only the age rangeand know someone who had or has leprosy is able to explain the anti-NDO-HSA seropositivity difference. And for the LID-1 no variable explained the anti-LID-1 seropositivity difference. All serological tests analyzed can assist in the differentiation and characterization of MB leprosy and the identification of individuals exposed to M. leprae, butNDO-LID performed better in identifying these individuals and PB patients, when compared to the tests involving the LID-1 and NDO-HSA antigens separately, therefore provides additional benefit to these antigens and could be used as an auxiliary tool in epidemiologicalsurveillance of leprosy.